Strength is relevant: experimental evidence of strength as a marker of commitment - Boulat, Kira; Maillat, Didier (Frontiers in Communication, 2023)
ABSTRACT When relevance theory (Sperber & Wilson 1995) tried to express the underlying processes involved during interpretation, they posited a process of context elaboration in which interpretation is seen as a path of least effort leading to the selection of a set of most salient contextual assumptions and implications. In this view, contextual assumptions are not randomly scattered in the hearer’s cognitive environment during this context elaboration process. Instead, Relevance Theory claims that there are some organising principles ordering contextual assumptions and determining which assumptions will be more likely to be accessed first in the process. The focus of this paper is on one such organising principle captured by the notion of strength. Sperber & Wilson (1987: 701) define it as the degree of “confidence with which [an] assumption is held”. While this notion has been posited right from the early days of Relevance theory, it has been left relatively untouched in relevance-theoretic accounts. In this paper, we will assess the explanatory potential of the notion of strength by linking it to the much-debated range of phenomena understood as related to commitment, i.e. the degree of speaker involvement in the truth of their utterance. Our goal will be to argue for a theoretical account of strength, in which strength is regarded as a cognitive marker of commitment, and more generally of the epistemic value of an utterance. In order to support this claim, we will present a series of original experimental designs in which we manipulated the level of speaker commitment in the information conveyed by their utterance. We predicted, on the basis of the theoretical model put forward, that such a manipulation would impact the level of strength. This cognitive effect, it is claimed, can in turn be measured through a recall task. We present results which support this model and discuss its implications.